Hubungan Dukungan Keluarga dengan Motivasi Pasien Pasca Stroke Melakukan ROM Aktif di RSUD DR. A Dadi Tjokrodipo - Andriani, Mellia; Agustriyani, Feri (Journal of Current Health Sciences, 2021)
Stroke is the third leading cause of disability worldwide. At RSUD Dr. A Dadi Tjokrodipo, stroke is the second largest disease after diabetes, in the last three months (June-July) patients can reach 25-30 people. Stroke has an impact that can affect a person's activities. In the recovery or rehabilitation phase (active ROM), the family must be actively and thoroughly involved because the strength and motivation of oneself and even those closest to them are needed by the patient. The research objective was to determine the correlation between family support and motivation of post-stroke patients on doing active ROM at Regional Hospital Dr. A Dadi Tjokrodipo. This research type is quantitative. This research used an analytic survey method with a cross-sectional approach. The population of this research were all post-stroke patients at Dr. A Dadi Tjokrodipo Regional Hospital Bandar Lampung City in January 2021 as many as 33 people. The total sample population was 33 people. The data analysis used the chi-square test. The analysis result showed the frequency distribution of family support, from the 33 respondents studied as many as 20 respondents (60.6%) stated that the family was supportive, 17 respondents (51.5%) had low motivation to do active ROM. There is a correlation between family support and motivation of post-stroke patients on doing active ROM at Regional Hospital Dr. A Dadi Tjokrodipo Bandar Lampung with p-value 0.046. It is expected that the nurse will support the family to motivate, give attention and ensure the patient/family about the movements that must be done during physiotherapy so, they can be trained outside the therapy schedule in order to support the patient's recovery.